Persepsi Masyarakat terhadap Bantuan Langsung Tunai (BLT) pada Masa Pandemi Covid-19 - Reptiana, Rofiqoh Prepti; Widiantoro, Didik; Sari, Wina Diana; Desvianti, Erika; Arezah, Ersaliya (Journal of Islamic and Contemporary Psychology, 2022)
Since the Corona Virus Disease-2019 (COVID-19) pandemic was officially declared to have entered Indonesia, in March 2020. This outbreak had an impact on the social and economic consequences of the Covid-19 pandemic which also affected the level of public welfare. This is due to the limitation of economic activity which at a macro level reduces economic growth and causes many people to lose their jobs, thereby potentially increasing the number of poor people. Based on this, the Government seeks to provide direct cash assistance for the community from the Village Fund or called BLT-Village Fund to reduce the burden on the poor due to the impact of Covid-19. BLT-Dana Desa is financial assistance sourced from the Village Fund and is intended for the poor and vulnerable who have difficulty meeting their daily needs, especially due to the Covid-19 outbreak. Village Fund Cash Direct Assistance (BLT-Village Fund) in Harapan Jaya Village, Central Bunguran District, Natuna Regency in 2020, for people who receive Village Fund Cash Direct Assistance (BLT) in Harapan Jaya Village, Bunguran Tengah District, Natuna Regency in 2020. quite a lot, namely with a total allocation of the number of people who receive as many as 225 Family Heads. The purpose of this study was to determine the perception of the recipient community towards the Direct Cash Assistance (BLT) program during the Covid-19 Pandemic in Harapan Jaya Village, Central Bunguran District, Natuna Regency. This research was conducted with descriptive qualitative methods, namely interviews and observations using purposive sampling technique. Data analysis technique using Milles and Huberman theory, namely redcing, presenting data, and concluding data. The results of this study indicate that the perceptions of the four subjects to feel the benefits of BLT are different.